1941
DOI: 10.2307/1787399
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of a Temperate Glacier

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1952
1952
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…flow.1 0 The strain rate became detectable at approximately 10 m. depth and increased rapidly at depths exceeding 30 m. These values are those set forth by Orowan 9 in his assumption of the yield stress of ice and by Seligman 13 in his work on the depth of crevasses.…”
Section: Contraction Of Tunnel Sectionsmentioning
confidence: 74%
See 1 more Smart Citation
“…flow.1 0 The strain rate became detectable at approximately 10 m. depth and increased rapidly at depths exceeding 30 m. These values are those set forth by Orowan 9 in his assumption of the yield stress of ice and by Seligman 13 in his work on the depth of crevasses.…”
Section: Contraction Of Tunnel Sectionsmentioning
confidence: 74%
“…Since this situation persisted in August and was present again in December, the assumption that the temperature there never quite came up to 0 0 C. throughout the past year seems a reasonable one. 13 ,18 The inner zone of 0 0 C. was distinguished by water inflows and numerous puddles on the tunnel flo or, puddles which were found and remained unfrozen in December. A relatively small decrease in temperature was noted in the transition from the ice to one of the small isolated air gapS' between the ice and rock-bed.…”
Section: Temperaturesmentioning
confidence: 99%
“…According to Colbeck and others (1978), the initial grain-size has a significant effect on the densification rate of wet snow; therefore it was determined in the light of the observed grain-size of firn in temperate glaciers and per ennial snow patches. Many measurements of grain-size distribution in temperate firn showed that the diameter of ice grain did not usually exceed 2 mm (Seligman, 1941;Vallon and others, 1976;Kawamura and others, 1989). Thin sections of snow samples used for the tests were made to measure the initial grain-size (area-equivalent diameter) distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The British seem to practice this with particular success. Take, for example, Gerald Seligman's (1941) Jungfraujoch research program in glaciology, which enlisted the talents of Nobel laureate-to-be Max Perutz (Perutz & Seligman 1939), among others. Similar results attended a program of field research on the Austerdalsbrea in Norway, which led to major glaciological contributions from British physicists John Nye (1952Nye ( , 1960Nye ( , 1963 of Bristol and John Glen (1955Glen ( , 1956) of Birmingham.…”
Section: Pedagogical Value Of Fiem Workmentioning
confidence: 99%